ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI ABNORMAL RETURN SAHAM PADA PERUSAHAAN PERBANKAN DAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Permana, Sidiq Jati (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: This research aims to analyzes the effect of profitability (NPM and ROE) and leverage (DER and DR) partially to stock abnormal returns at the Banking and Insurance Companies Listed Indonesia Stock Exchange, also to analyze the different effect of profitability (NPM and ROE) and leverage (DER and DR) on stock abnormal returns at the Banking and Insurance Companies Listed Indonesia Stock Exchange. Data used in this research are secondary data collected from ICMD and Annual Report of Companies in Indonesia Stock Exchange at 2010 – 2014, and www.yahoofinance.com. The populations in this research are the Banking and Insurance Companies Listed in Indonesia Stock Exchange. Sampling method is purposive sampling. The model of analysis used in this research is multiple linier regressions. Results of this research show that NPM have positively and significant effet on stock abnormal return at the Banking and Insurance Companies Listed Indonesia Stock Exchange. ROE have positively and significant effect on stock abnormal returns. DER has negatively but not significant effect on stock abnormal returns at the Banking and Insurance Companies Listed Indonesia Stock Exchange. DR has positively but not significant effect on stock abnormal returns at the Banking Companies Listed Indonesia Stock Exchange. While for the insurance companies, DR has negative effect but not significant on stock abnormal returns. There are differences in the effect of profitability (NPM and ROE) and leverage (DER and DR) to the stock abnormal returns on the Banking Companies Listed Indonesia Stock Exchange .Keywords: profitability, leverage, Net Profit Margin/NPM, Return on Equity/ROE, Debt to Equity Ratio/DER, Debt Ratio/DR, and abnormal return